A contributing factor of maternal pregnancy depression in the occurrence of stunting on toddlers - Tanti Apriliana (PAGEPress Publications, 2021)
Background: Toddlers are a vulnerable population to nutritional problems including stunting. Stunting can have negative impact on toddlers' health. One of the factors causing stunting in toddlers is maternal pregnancy depression. This study aims to determine the relationship between maternal pregnancy depression and the incidence of stunting in toddlers. Design and Methods: The research design employed a descriptive correlative with quota sampling technique. The research respondents were 140 mothers of toddlers in Indonesia such as West Java, East Java, Jakarta, Yogyakarta, Bali, North Sumatra, Riau, South Kalimantan, West Kalimantan, North Sulawesi, NTT, NTB, Maluku, Papua. The data were collected by using demographic method and the Edinburgh Postpartum Depression Scale (EPDS). The statistical tests employed correlation tests. Results: The analysis reveal that 26.4% toddlers in this study are stunted and 73.6% were not stunted. Maternal pregnancy depression has a significant relationship with the incidence of stunted toddlers (p = 0.044; r = 0.170). Conclusions: The results of this study are expected to underlie the development of mental health promotion to prevent stunted toddlers against maternal depression and preventive programs. In addition, the research is expected to underly provision of curative and rehabilitative programs for stunted toddlers.